2005
DOI: 10.1007/s10526-004-0461-9
|View full text |Cite
|
Sign up to set email alerts
|

Field assessment of Fusarium oxysporum based mycoherbicide for control of Striga hermonthica in Nigeria

Abstract: Fusarium oxysporum (isolate PSM 197) based mycoherbicide was evaluated for its efficacy under field conditions in trials conducted during 1999-2001 cropping seasons in the Nigerian savanna. In the 1999 cropping season, spot application of 5-10 g of mycoherbicide was found to give effective control of Striga hermonthica. Results of on-farm trials at Barhim and Dutsen-Ma areas showed the application of the mycoherbicide to significantly (p ¼ 0.05) increase stand count at both 3 weeks and at harvest, reduced Stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Pests such as Striga and stem borers can have devastating consequences for grain yield throughout Africa. In addition to herbicide application (Carsky et al 1994;Tuinstra et al 2009) and the use of fungal spores (Marley and Shebayan 2005;Venne et al 2009), crop rotation has been demonstrated to control Striga and improve yield. Carsky et al (2010) demonstrated maize-soybean rotations reduced the Striga-derived yield decline in maize relative to a continuous grain rotation; the authors suggest the control mechanism is soybean reduction of the Striga viable seedbank by exuding a germination stimulant.…”
Section: Contextual Agricultural Developmentmentioning
confidence: 99%
“…Pests such as Striga and stem borers can have devastating consequences for grain yield throughout Africa. In addition to herbicide application (Carsky et al 1994;Tuinstra et al 2009) and the use of fungal spores (Marley and Shebayan 2005;Venne et al 2009), crop rotation has been demonstrated to control Striga and improve yield. Carsky et al (2010) demonstrated maize-soybean rotations reduced the Striga-derived yield decline in maize relative to a continuous grain rotation; the authors suggest the control mechanism is soybean reduction of the Striga viable seedbank by exuding a germination stimulant.…”
Section: Contextual Agricultural Developmentmentioning
confidence: 99%
“…As a rule, Fusarium , mainly F. oxysporum , isolated from S. hermonthica selectively attack Striga spp. ( Abbasher and Sauerborn, 1992 ; Ciotola et al, 1995 ; Savard et al, 1997 ; Abbasher et al, 1998 ; Marley et al, 1999 ; Amalfitano et al, 2002 ; Marley and Shebayan, 2005 ; Elzein and Kroschel, 2006 ; Schaube et al, 2006 ; Venne et al, 2009 ; Watson, 2013 ). An isolate from Mali in combination with fertilizer inputs successfully prevented Striga emergence and resulted in 400% increase of sorghum dry matter ( Ciotola et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…Others upregulate the expression of phosphate transporters in their host plant, enhancing P uptake (Yadav et al., 2010 ), or producing toxic substances that detract herbivores from their hosts (Pozo et al., 2021 ). Finally, certain endophytic strains act as biocontrollers of parasite weeds by obstructing their xylem vessels (Marley & Shebayan, 2005 ) or inhibiting seed germination (Anteyi et al., 2022 ). This fascinating biocontrol ability allowed to develop mycoherbicides, efficient products for controlling parasitic weeds (Sands & Pilgeram, 2009 ).…”
Section: Fungi As Plant Growth‐promoting Microorganismsmentioning
confidence: 99%